The Irish Financial Crisis: The Systematic Failings of the Irish Institutional and Banking Systems - McAdam, Gareth (2011)
Prior to 2007, Ireland evolved from one of the poorest countries in Western Europe to one of the most successful (Dorgan, 2006). Now in 2011, in the aftermath of the global financial crisis, the Irish economy is financially crippled with a banking system completely reliant on government support. A financial sector bailout coupled with deteriorations in public finances has resulted in the Irish government accepting an €85 billion economic rescue package from the IMF and the European Central Bank.